Psychological Impact of the COVID-19 Pandemic on Healthcare Professionals in Tunisia: Risk and Protective Factors - Hammami, Ahmed Sami; Jellazi, Mohamed; Mahjoub, Lobna; Fedhila, Maya; Ouali, Sonia (Frontiers in Psychology, 2021)
Background: The aims of our study were to evaluate the magnitude of different psychological outcomes among Tunisian healthcare professionals (HCPs) during the first wave of the COVID-19 pandemic, and to identify the associated factors. Methods: HCPs completed a cross-sectional questionnaire during a 3-week period in the first wave of the COVID-19 pandemic in Tunisia. The survey collected demographic information, factors that may interfere with the psychological outcomes, behavioral changes, and mental health measures. The latter were assessed with 3 scales: the 7-item Insomnia Severity Index, the 2-item Patient Health Questionnaire, and the 2-item Generalized Anxiety Disorder instrument. Multivariable logistic regression was conducted to identify factors associated with psychological outcomes. Results: A total of 503 HCPs successfully completed the survey, and 493 agreed to enroll in the study: 411(83.4%) physicians, 323(64.2%) women, and 271(55%) with a second-line work position. A significant proportion of HCPs had anxiety (35.7%), depression (35.1%), and insomnia (23.7%). Females, those with a psychiatric history, and those using public transportation had higher proportions for overall symptoms compared to other groups, e.g. depression in 44.9% of female participants vs. 18.2% of male participants (p=0.00). Those with a previous medical history and nurses had more anxiety and insomnia compared to other groups, e.g. anxiety in 45.1% of nurses, 36.1% of interns/residents, and 27.5% of attending physicians (p=0.04). Multivariable logistic regression showed that female gender was a risk factor for all psychological outcomes, whereas psychiatric history was a risk factor for both anxiety and insomnia (OR=2.86, 95% CI 1.78-4.60,p=0.00 for insomnia). Using protective equipment was associated with a lower risk for depression (OR=0.41, 95% CI 0.27-0.62, p=0.00) and anxiety. Physical activity was also protective against depression and anxiety (OR=0.41, 95% CI 0.25-0.67,p=0.00). Conclusion: Psychological symptoms are usually dismissed by HCPs, although the COVID-19 pandemic played a major role in exacerbating this burden. Prompt psychological support should be endorsed and simple measures such as physical activity and ensuring the availability of personal protective equipment are paramount to improve mental health outcomes and the quality of care provided to patients. Keywords: Psychological symptoms, mental health, healthcare professionals, COVID-19 pandemic, risk factors, protective factors.